دراسة المقطع العرضي التفاضلي لانتثار كومبتون - جبور, جبور; ملحم, جهاد; ياسين, سهى (Latakia University Journal -Basic Sciences Series, 2013)
تمَّ في هذا العمل، دراسة انتثار (تبعثر) كومبتون باستخدام أشعة غاما (فوتونات) بطاقة (662 keV)، الصادرة عن منبع مُشع من السيزيوم-137 (137Cs) شدته (3,33×105 Bq)، المتبعثرة على قضيب من الألمنيوم (المُبعثر كناثر). تمَّ أيضاً قياس المقطع العرضي التفاضلي ومن ثمَّ مقارنة النتائج التجريبية بالنتائج النظرية للمقطع العرضي التفاضلي التي تمَّ حسابها باستخدام علاقة كلين-نيشينا. In this work, it has been studied Compton Effect using the 662 keV gamma rays from a radioactive source of cesium-137 (137Cs) intensity (3.33×105 Bq) on Aluminum rod (who plays scatter). It has been measured the differential cross section, and the experimental values of differential cross section compared with theoretical values given by Klein - Nishina equation.